Making Digital Money “Work” for Low-Income Users: Critical Reflections for HCI - Hulikal Muralidhar, Srihari (International Journal of Mobile Human Computer Interaction, 2019)
This paper adds to the research on digitization and money in HCI. By presenting a case of rickshaw drivers in India and their use of Ola, an app-based taxi service like Uber, and Ola Money, an embedded m-wallet, this paper makes a threefold contribution. First, it shows how cash and digital money are not simply different manifestations of the ‘same’ money for users. They provide distinct affordances and have different meanings and values, yielding rich insights for design. Second, it seeks to highlight the hidden work done by users around making digital money ‘work’ for them. In doing so, it calls for a broader understanding of ‘moneywork’ that goes beyond a temporal analysis, through the concept of ‘mobility work’. Finally, it highlights the role of ‘friction’ in design. Friction is crucial to users’ negotiation of the trade-off between consumption and saving, and can be leveraged to provoke reflection and user-awareness.